Der Vertrag von Sèvres Vertragstext und Analyse des Friedensschlusses mit der Türkei vom 10. August 1920 im Kontext der Pariser Vorortverträge - Gassner, Miriam (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The Peace Treaty with Turkey, concluded in 1920 in Sèvres near Paris in 1920 is, although it never came into force, one of the most important international law treaties of our time. Aimed at reshaping the Middle East, it enabled the expansion of the British Empire and laid the foundation for a new international legal order. This work contains the first complete translation of the Treaty of Sèvres into German, provides an overview of its genesis, and analyzes the peace treaty with Turkey in the context of the Paris Suburb Treaties.